2016
DOI: 10.33961/jecst.2016.7.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Vanadium Titanates as a Negative Electrode for Lithium-ion Batteries

Abstract: Amorphous vanadium titanates (aVTOs) are examined for use as a negative electrode in lithium-ion batteries. These amorphous mixed oxides are synthesized in nanosized particles (<100 nm) and flocculated to form secondary particles. The V 5 + ions in aVTO are found to occupy tetrahedral sites, whereas the Ti 4 + ions show fivefold coordination. Both are uniformly dispersed at the atomic scale in the amorphous oxide matrix, which has abundant structural defects. The first reversible capacity of an aVTO electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…[119][120][121][122][123][124][125][126][127] Amorphous nanoparticles are of interest due to their applications in catalysis, optics, magnetism, bioactivity, electrochemistry, and nanocomposites. [128][129][130][131][132][133][134] In particular, there are cases within the water oxidation catalysis literature where the amorphous materials have produced superior catalytic activity to their crystalline counterparts. 135,136 For the formation of amorphous nanoparticles, there are a limited number of studies that use synchrotron XAFS or SAXS techniques to investigate the local structural changes of what are typically amorphous nanoparticles at least initially.…”
Section: Additional Systems Of Interest: Perovskites Quaternary Nanocrystals Amorphous Nanoparticles and Carbon Dotsmentioning
confidence: 99%
“…[119][120][121][122][123][124][125][126][127] Amorphous nanoparticles are of interest due to their applications in catalysis, optics, magnetism, bioactivity, electrochemistry, and nanocomposites. [128][129][130][131][132][133][134] In particular, there are cases within the water oxidation catalysis literature where the amorphous materials have produced superior catalytic activity to their crystalline counterparts. 135,136 For the formation of amorphous nanoparticles, there are a limited number of studies that use synchrotron XAFS or SAXS techniques to investigate the local structural changes of what are typically amorphous nanoparticles at least initially.…”
Section: Additional Systems Of Interest: Perovskites Quaternary Nanocrystals Amorphous Nanoparticles and Carbon Dotsmentioning
confidence: 99%
“…However, merely increasing the ion-storage sites is not sufficient to increase the capacity. An adequate number of electrons are also required to attain local neutrality during cycling ( 25 ). It is equally important to improve the local electron-transfer ability of active sites to quickly achieve charge balance, especially for the storage of high–charge density multivalent ions.…”
Section: Introductionmentioning
confidence: 99%
“…Faster lithiation in bronze TiO 2 compared with anatase originates from the presence of open and freely accessible parallel channels on the surface. 19,28 Amorphous metal oxide, including TiO 2 , has recently received increasing attention due to its open structure to accommodate Li + , 29,30 and higher capacities and rate capabilities have been reported for amorphous TiO 2 compared to crystalline TiO 2 . 31,32 Broad lithiation and de-lithiation peaks, resembling more capacitive storage, are observed in cyclic voltammetry (CV) measurements involving amorphous TiO 2 electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure also determines the rate of Li + migration in TiO 2 . Faster lithiation in bronze TiO 2 compared with anatase originates from the presence of open and freely accessible parallel channels on the surface. , Amorphous metal oxide, including TiO 2 , has recently received increasing attention due to its open structure to accommodate Li + , , and higher capacities and rate capabilities have been reported for amorphous TiO 2 compared to crystalline TiO 2 . , Broad lithiation and de-lithiation peaks, resembling more capacitive storage, are observed in cyclic voltammetry (CV) measurements involving amorphous TiO 2 electrodes. These broader peaks are more evident with amorphous TiO 2 nano-sized structures, which possess more free space on the surface in addition to the open spatial channels in the bulk. , Jiang et al reported that Li + diffusion in amorphous TiO 2 nanotubes is 2 orders of magnitude faster than that in anatase TiO 2 nanotubes .…”
Section: Introductionmentioning
confidence: 99%